Research on dynamic erosion mechanism of submarine landslide: Review and prospects - Yueping YIN; Wenpei WANG; Aiguo XING; Bolin HUANG; Bin LI; Leiyan HAN; Shaoqiang JIN; Yong YANG; Chenyang ZHANG (Zhongguo dizhi zaihai yu fangzhi xuebao)
The geological hazards of submarine landslides can cause serious damage to infrastructure such as offshore wind power, submarine optical cables, and marine platforms, posing a serious challenge to the major strategic task of building a maritime power and ensuring the geological safety of marine engineering. The article systematically reviews the research process of submarine landslide turbidity current geological hazards, summarizes the dynamic characteristics of submarine landslide-turbidity flow chain, dynamic erosion types, mechanisms of triggering, evolution, migration, erosion and sedimentation, theoretical models of erosion, and the influence of complex landforms such as uplift, canyons, and basins. A novel dynamic erosion approach is put forward of submarine landslide-turbidity flow chain, including quantitative, multiphase, whole process, erosion flow-state transformation. Finally, in view of the development of major projects such as offshore wind power, marine resource development, marine transportation, and marine engineering equipment, the geological model and identification technology are discussed of the erosion-prone structure of submarine landslide landslide-turbidity flow chain, as well as the composite, overlapping, and heterogeneous dynamic erosion mechanic model of the disaster chain, and the issues of prevention and control of boundary layer dynamic erosion.